URINARY RETENTION EDUCATIONAL TOOLKIT: STRATEGIES AND RESOURCES TO REDUCE CATHETER-ASSOCIATED COMPLICATIONS IN LONG-TERM CARE FACILITIES - Keim, Cassidy (My University, 2016)
Urinary retention is the inability to completely void the bladder. The condition can either be acute or chronic. Causes of urinary retention include obstruction, infection and inflammation, pharmacological, neurological, or trauma. Urinary retention is common in both sexes, but is especially prevalent in aging men due to enlargement of the prostate which obstructs urine flow. This condition is usually managed by catheterization, specifically indwelling (e.g., Foley catheters) catheters in long-term care facilities. These long-term indwelling catheters increase a person’s risk of acquiring an infection. These issues are especially important in long term-care facilities (LTCF), where between 7.5% and 10% of residents have indwelling catheters. Catheter use increases rates of catheter-associated urinary tract infections that can be life threatening in older individuals. During my field experience at the Kansas Department of Health and Environment (KDHE), I developed a toolkit aimed at addressing the issue of urinary retention among long-term care residents. For this project, I worked closely with my mentors Joseph Scaletta and Brenda Groves. The educational toolkit provides an overview of urinary retention, current assessment and management practices, catheter complications, educational resources for caregivers and family members, and prevalent policies concerning urinary retention.
Keywords: Urinary retention; Toolkit; Long-term care; Catheter-associated complications; Resident; Kansas Department of Health and Environment